Ti-Zr-Al alloy and preparation method thereof

By adding an appropriate amount of Al and Zr elements to the titanium alloy, and using vacuum consumable arc furnace and electromagnetic stirring technology, the shortcomings in strength, plasticity and cutting performance of titanium alloy are solved, and high-quality ingot production is achieved.

CN119876693APending Publication Date: 2025-04-25JIANGSU KANGTAI TECH CO LTD +1

Patent Information

Application Number
CN202510360469.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing titanium alloys have shortcomings in strength, plasticity and cutting properties, and are prone to sticking to the knife during turning and processing, and aluminum elements are prone to volatilization and segregation during smelting.

Method used

By adding 0.10-0.50% Al and 0.40-0.80% Zr elements to the titanium alloy, the alloy elements are accurately proportioned, and melted using a vacuum consumable arc furnace, and smelting is carried out through electromagnetic stirring and multiple melting to control the uniformity of the components and reduce segregation.

Benefits of technology

It improves the strength and processing performance of the alloy, reduces the content of impurities, ensures the quality of the ingot, improves the cutting performance and reduces the occurrence of sticking knife phenomenon.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876693A_ABST
    Figure CN119876693A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Ti-Zr-Al alloy, which comprises the following steps: determining the ratio value of each alloy element according to the target component range of the Ti-Zr-Al alloy, and selecting sponge titanium, sponge zirconium, a titanium-iron alloy, titanium dioxide and aluminum shots as raw materials; weighing the titanium sponge and the intermediate alloy, and uniformly mixing the titanium sponge and the alloy raw material to form a to-be-pressed raw material; pressing into electrode blocks, and stacking and welding the electrode blocks into a consumable electrode; and the consumable electrode is smelted through a vacuum consumable electric arc furnace, so that the Ti-Zr-Al alloy is prepared. By controlling the chemical components of all the elements in the titanium alloy, the composition proportion of the titanium alloy meets the batching requirement of the titanium alloy cast ingot, the content of impurity elements in the Ti-Zr-Al titanium alloy cast ingot is effectively controlled, and the quality of the titanium alloy cast ingot is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of smelting, and in particular to a method for preparing a Ti-Zr-Al alloy. Background Art

[0002] Titanium alloys have the advantages of high specific strength and good corrosion resistance, and their applications in the fields of aviation and shipbuilding are gradually expanding. Aluminum and zirconium are two widely used additive elements in the preparation of titanium alloy materials. Reasonable selection of aluminum and zirconium content can effectively refine the casting structure of the material, improve hot working processability, deformation uniformity, etc. Therefore, the influence of aluminum and zirconium on titanium alloys is becoming more and more important.

[0003] However, the existing titanium alloys still need to be improved in terms of strength, plasticity and cutting performance, and tool sticking often occurs during turning.

[0004] Furthermore, in the prior art, since the melting point of aluminum is relatively low (660.32° C.), the aluminum element is easily volatilized during the smelting process, resulting in the segregation of the aluminum element during the solidification process. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects in the prior art and provide a method for preparing a Ti-Zr-Al alloy.

[0006] To achieve the above-mentioned purpose, the technical solution of the present invention is as follows: a Ti-Zr-Al alloy, characterized in that the following components by weight percentage include: 0.1-0.5% aluminum; 0.4-0.8% zirconium; 0.30-0.40% iron; 0.30-0.40% oxygen; 0-0.08% carbon; 0-0.05% nitrogen; 0-0.015% hydrogen; the rest is composed of titanium and unavoidable impurities.

[0007] A method for preparing a Ti-Zr-Al alloy, characterized in that the ratio of each alloy element is determined according to a target composition range, and the alloy raw material to be added is determined; sponge titanium and the alloy raw material are weighed, and the sponge titanium and the alloy raw material are evenly mixed to form a raw material to be pressed; Pressing the raw material to be pressed into an electrode block, and stacking a plurality of the electrode blocks into a consumable electrode to be welded; The consumable electrode is welded and smelted in a vacuum consumable arc furnace to prepare a Ti-Zr-Al alloy.

[0008] The present invention adds 0.10-0.50 Al and 0.40-0.80 Zr elements to the titanium alloy to improve the strength of the alloy and improve some processing properties. By accurately proportioning the elements in the titanium alloy, the composition ratio meets the composition requirements of the titanium alloy, effectively controls the content of impurity elements in the Ti-Zr-Al titanium alloy ingot, and ensures the quality of the titanium alloy ingot.

[0009] Furthermore, the step of pressing the raw material to be pressed into an electrode block, and stacking a plurality of the electrode blocks into a consumable electrode to be welded comprises: The raw material to be pressed is pressed into an electrode block by an arc-shaped punch of a hydraulic press, one of the two sides of the electrode block is an arc surface, and the other side of the two sides of the electrode block is a plane; the planes of two electrode blocks are fitted together to form a section of the consumable electrode, and multiple sections of the consumable electrodes are stacked into a consumable electrode to be welded; the height of the cross section of the electrode block is 225-290mm, the width of the cross section of the electrode block is 420-540mm, and the diagonal length of the cross section of the consumable electrode is 480-620mm.

[0010] like Figure 1 As shown in the figure, when the hydraulic press presses the electrode block, the punch of the hydraulic press squeezes the raw material to be pressed in the die. Since the punch is in an arc shape, as the punch continuously squeezes the raw material to be pressed, the powder particles in the raw material to be pressed have good overall fluidity, less displacement shear area, and the surface cracks of the electrode block are effectively eliminated. The compressed side of the raw material to be pressed forms the arc surface of the electrode block, and the other side is squeezed with the bottom plane of the die to form a flat surface.

[0011] Furthermore, the step of welding with the consumable electrode comprises: The consumable electrode is welded by an electron beam welding box, or by a plasma welding box; the electron beam welding box or the plasma welding box is provided with a plurality of welding guns, the plurality of welding guns are arranged at intervals along the length direction of the consumable electrode, the distance between adjacent welding guns is L, the length of a section of the consumable electrode is L1, L=L1*n, n is a positive integer, and the plurality of welding guns weld the gaps between the sections of the consumable electrode to form a transverse weld. In this way, the plurality of welding guns can correspond to the gaps between the plurality of sections of the consumable electrode one by one, and the plurality of gaps can be automatically welded at the same time, thereby improving the welding efficiency.

[0012] Further, the step of welding the consumable electrode by an electron beam welding box or welding the consumable electrode by a plasma welding box includes: The consumable electrode is welded along the length direction of the consumable electrode by the electron beam welding box or the plasma welding box to form a longitudinal weld, and a plurality of the longitudinal welds are arranged at intervals. The longitudinal welds are arranged to enhance the connection strength between the electrode blocks and avoid the block falling during the smelting process.

[0013] Furthermore, when the consumable electrode is welded by the electron beam welding box, the welding current is 2A-3A and the welding voltage is 20KV-25KV. When the electron beam welding box is used for welding, the energy density is very high, the electron beam can be focused to a very small diameter, and a large amount of heat can be generated in a very small area. For consumable electrode welding, this high energy density can achieve high-precision welding, which can make the weld very narrow and have a large aspect ratio. For example, when welding some consumable electrodes with high dimensional accuracy requirements, excessive material melting can be avoided, reducing the impact on the original shape and size of the electrode.

[0014] At a voltage of 20KV-25KV and a current of 2A-3A, the electron beam can quickly melt and solidify the metal. Since the electron beam has concentrated energy, the heat input is relatively concentrated and efficient, and the welding process can be completed in a short time. This helps to improve production efficiency and can greatly shorten the welding time.

[0015] Electron beam welding produces a very small heat-affected zone. Because the heat is mainly concentrated in the area where the electron beam is focused, the thermal effect on the surrounding materials is small. For consumable electrodes, this means that other parts of the electrode are less affected by heat during the welding process, which can reduce thermal deformation and thermal stress, and prevent the electrode from cracking due to thermal stress after welding.

[0016] Furthermore, when the consumable electrode is welded by the plasma welding box, the welding current is 400A-600A and the welding voltage is 60V-90V.

[0017] When plasma welding uses a welding current of 400A-600A and a welding voltage of 60V-90V, it can generate a large arc energy. This higher energy can make the weld obtain a larger penetration and a relatively wider weld. For some consumable electrodes with large sizes or high weld strength requirements, plasma welding can ensure that the weld has sufficient fusion depth and width, and improve the overall strength and connection reliability of the electrode.

[0018] Compared with electron beam welding, plasma arc has better stability and stiffness, and the assembly accuracy requirements for consumable electrodes are relatively low. During the welding process, even if the butt gap of the consumable electrode has a certain deviation, the plasma arc can fill the gap well and form a weld of qualified quality, and the requirements for the consumable electrode fixture are relatively low.

[0019] In addition, the cost and maintenance difficulty of plasma welding box are lower than that of electron beam welding box.

[0020] Furthermore, the step of determining the ratio of each alloy element according to the target composition range of the Ti-Zr-Al alloy includes: determining the ratio of each alloy element according to the target composition range of the Ti-Zr-Al alloy as Al: 0.3%, Zr: 0.6%; Fe: 0.35%; O: 0.30%. Considering the element segregation, the target value of Fe is set to 0.35%, and the target value of Zr is set to 0.6%; considering the increase in oxygen during the smelting process, the target value of O is set to 0.30%; considering the large amount of Al volatilization during the VAR smelting process, the target value of Al is set to 0.30%.

[0021] Further, the step of melting the consumable electrode by a vacuum consumable arc furnace includes: the outer diameter of the consumable electrode cross section is 480 mm, the consumable electrode is melted by a crucible with a diameter of 580 mm to prepare a primary ingot, the melting current is 14-18KA, and the melting voltage is 30-35V; the primary ingot is melted by a crucible with a diameter of 650 mm to prepare a secondary ingot, the melting current is 20-24KA, and the melting voltage is 30-35V; the secondary ingot is melted by a crucible with a diameter of 720 mm to prepare a Ti-Zr-Al alloy, the melting current is 25-29KA, and the melting voltage is 30-35V. The three melting processes make the uniformity of the alloy elements good and the segregation degree low.

[0022] Furthermore, the step of determining the alloy raw materials to be added includes: adding Al element in the form of aluminum beans; adding Zr element in the form of zirconium sponge; adding Fe element in the form of titanium-iron alloy or iron nails; and adding O element in the form of titanium dioxide.

[0023] Aluminum beans are a relatively cheap and easy to handle form. Compared with other forms such as aluminum powder, aluminum beans have a lower cost. By adding the Fe element in the form of ferrotitanium alloy, the uniformity of the Fe element in the ingot can be improved. Since the procurement cost of iron nails is lower than that of ferrotitanium alloy, the raw material procurement cost can be reduced by adding the Fe element in the form of iron nails. It should be noted that the iron nails are iron nails with a diameter of less than 3 mm and a length of less than 20 mm, so as to improve the uniformity of the Fe element in the ingot on the basis of reducing the raw material procurement cost.

[0024] Further, the step of weighing the titanium sponge and the alloy raw material, and uniformly mixing the titanium sponge and the alloy raw material to form a raw material to be pressed comprises: The titanium sponge and the alloy raw material are weighed by an automatic mixer, and the titanium sponge and the alloy raw material are mixed evenly by a mixer to form a raw material to be pressed. The mixing time of the mixer is 30-90S, and the weight of the raw material to be pressed is 140-200kg. The weighing is accurate and efficient by the automatic mixer. By setting the mixing time to 30-90S and the weight of the raw material to be pressed to 140-200kg, it is ensured that the titanium sponge and the alloy raw materials in the raw material to be pressed are mixed evenly.

[0025] Furthermore, electromagnetic stirring is used in the VAR smelting process to enhance melt convection and promote uniform distribution of alloy elements. The electromagnetic stirring includes an electromagnetic induction coil arranged outside the water jacket, the coil is connected to a power source, and is provided with a sensor and a controller to monitor and adjust the magnetic field strength and direction. The characteristics of the magnetic field are controlled by adjusting the current size and direction to move the metal liquid in the titanium alloy molten pool.

[0026] The advantages and beneficial effects of the present invention are: 1. The present invention adds 0.10-0.50 Al and 0.40-0.80 Zr elements to the titanium alloy to improve the strength of the alloy and improve some processing properties. By accurately proportioning the elements in the titanium alloy, the composition ratio meets the composition requirements of the titanium alloy, effectively controls the content of impurity elements in the Ti-Zr-Al titanium alloy ingot, and ensures the quality of the titanium alloy ingot.

[0027] 2. Through the optimization of titanium sponge, reasonable method of adding intermediate alloy, reasonable consumable electrode size, reasonable smelting parameters and smelting times, a titanium alloy ingot containing aluminum and zirconium elements with a total weight of 3000-6000kg is prepared, and the composition uniformity is good after testing.

[0028] 3. The present invention effectively controls each smelting process by controlling the process parameters of VAR smelting, promotes the melting and uniform diffusion of raw materials in the VAR smelting process, prevents element segregation, prepares high-quality Ti-Zr-Al titanium alloy ingots without metallurgical defects, and improves the quality of Ti-Zr-Al titanium alloy ingots.

[0029] 4. In the last two smeltings of the three-time VAR smelting, the ingot is inverted as a consumable electrode for smelting, which effectively reduces the phenomenon of macro-segregation of elements. That is, when the second smelting is carried out, the primary ingot and the secondary ingot are melted from the head to the bottom, and the bottom of the primary ingot is the head of the secondary ingot, and the bottom of the secondary ingot is the head of the tertiary ingot. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a structural schematic diagram of the cross section of the consumable electrode in the present invention; Figure 2It is a schematic diagram of the circular arc punch of the hydraulic press pressing the raw material to be pressed in the embodiment of the present invention; Figure 3 is a front view of a consumable electrode in the present invention; Figure 4 It is a location diagram for sampling the two ingot products in the present invention; Figure 5 It is a schematic diagram of the placement of wedges in the VAR furnace of the present invention; Figure 6 This is a schematic diagram of the structure of the wedge in the VAR furnace of the present invention. Figure 1 ; Figure 7 This is a schematic diagram of the structure of the wedge in the VAR furnace of the present invention. Figure 2 ; Figure 8 It is a microstructure metal phase comparison diagram of the Ti-Zr-Al alloy in the present invention; In the figure: 1. electrode block; 2. consumable electrode; 3. longitudinal weld; 4. transverse weld; 5. arc surface; 6. head; 7. bottom; 8. crystallizer; 9. wedge; 10. bottom plate; 11. first side plate; 12. second side plate; 13. punch; 14. die; 15. raw material to be pressed; 21. rib plate; 22. scale line; 23. weight reduction hole. DETAILED DESCRIPTION

[0031] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0032] A Ti-Zr-Al alloy, characterized in that the following components are included by weight percentage: 0.1-0.5% aluminum; 0.4-0.8% zirconium; 0.30-0.40% iron; 0.30-0.40% oxygen; 0-0.08% carbon; 0-0.05% nitrogen; 0-0.015% hydrogen; the rest is composed of titanium and unavoidable impurities. Figure 8As shown in the figure, the left side a is the microstructure metallographic diagram of TA4 industrial pure titanium, and its average grain size is 6μm; the right side b is the microstructure metallographic diagram of Ti-Zr-Al alloy, and its average grain size is 4.5μm. It can be seen that after adding aluminum (Al) and zirconium (Zr) to the titanium alloy, the change in its microstructure will directly lead to significant differences in mechanical properties. Al is an α-phase stabilizing element. The atoms exist in the titanium matrix in the form of substitutional solid solution, causing lattice distortion, significantly improving the room temperature and high temperature strength of the alloy while maintaining a low density. Zr is a neutral element and has a large solid solubility in both α-titanium and β-titanium. Adding a small amount of zirconium can improve the matrix strength through solid solution strengthening, while maintaining good plasticity and avoiding increased brittleness. If the Zr content increases further, the room temperature strength continues to increase, but the plasticity will also decrease. Adding Al and Zr to the TA4 composition can improve the strength without significantly reducing the plasticity, and the cutting performance of the titanium alloy material is significantly improved, which can be better applied to the 3C electronics industry.

[0033] The following is an orthogonal experimental design for Al (0.1-0.5%) and Zr (0.4-0.8%) doped titanium alloys: Experimental groups: Using L9 (3^4) orthogonal table, select two key groups of variable combinations, including the benchmark group TA4, a total of 8 groups: Table 1

[0034] For the test of mechanical properties, tensile strength, yield strength, elongation and hardness are used for testing. The specific test data are shown in the following table: Table 2

[0035] The test results of cutting performance and knife sticking are as follows: Table 3

[0036] Based on the above experiments, it can be concluded that the limited range of this embodiment (Experiment 3 A2Z2, Al 0.1-0.5%, Zr 0.4-0.8%) has the following comprehensive advantages: Al / Zr synergistic strengthening effect: Tensile strength: For every increase of 0.1% Al + 0.2% Zr, the tensile strength increases by about 3-5%. For example, A1Z1→A2Z2: Al+0.1%, Zr+0.2%, the tensile strength increases from 700→767 MPa, +9.6%.

[0037] Yield strength: Al has a more significant effect on improving yield strength, with each 0.1% Al contributing about 2-3%. For example, A3Z1→A3Z2: Al remains unchanged, Zr+0.1%, yield strength 620→657 MPa, +6.0%.

[0038] Based on the above experiments, the plastic loss threshold of Ti-Zr-Al alloy can be obtained. Specifically, when Al>0.5% or Zr>0.8%, the elongation decrease rate accelerates. For example, the elongation of A3Z3 is 22%, while that of TA4 is 27%, -18.5%. The preferred A2Z2 (Al 0.3% + Zr 0.6%) in the target range (Al 0.1-0.5%, Zr 0.4-0.8%) is the best overall: its tensile strength is 767 MPa (+11.2%), yield strength is 610 MPa (+8.9%), elongation is 26.5% (only -1.9%), hardness is 267 HV (+6.8%), cutting force is 480 N (-4.0%), and surface roughness is 2.5 μm (-34.2%).

[0039] Strength-ductility product (UTS×EL): A2Z2 was 20,325 MPa·% (767×26.5), which was significantly higher than the over-limit group (such as A3Z3 was 17,600 MPa·%).

[0040] Strength-plasticity balance: The tensile strength increased by 11.2% (767 MPa), and the elongation only decreased by 1.9% (26.5%), which is significantly better than the over-limit group.

[0041] Optimized cutting performance: The hardness was increased to 267 HV, the cutting force decreased by 4% (480 N), the surface roughness was significantly improved (Ra 2.5 μm), and the friction coefficient decreased by 23.6% (0.42).

[0042] Economical: The hardness increase of 6.8% (267 HV) does not significantly increase the processing cost (compared with A3Z3 hardness 283 HV and A2Z3 hardness 320 HV, which require the use of more wear-resistant tools).

[0043] Knife sticking suppression effect: The friction coefficient (0.42) is 23.6% lower than that of TA4, and the chip fragmentation is obvious, which is better than other groups.

[0044] Summary of performance defects of the over-limit group: Al exceeds the limit (>0.5%): such as A3Z1 (Al 0.6% + Zr 0.4%), the elongation is 22% (-18.5%), the cutting force is 510N (+2.0%), and the surface roughness is worse than A2Z2.

[0045] Zr exceeds the limit (>0.8%): Cutting performance fluctuates. For example, the hardness of A2Z3 (Zr 1.0%) abnormally increases to 320 HV (+28%), and the cutting force is 535 N (+7.0%).

[0046] In summary, the range defined in this embodiment (Al 0.1-0.5%, Zr 0.4-0.8%) is the preferred range. Its strength is controllable: tensile strength ≤ +15%, yield ≤ +20% (actual tensile strength +11.2%, yield +8.9%) to avoid excessive embrittlement. At the same time, plasticity is retained: elongation ≥25% (actual 26.5%), meeting the toughness requirements of engineering parts. And it provides friendly processing performance: cutting force 480 N, surface roughness ≤2.5 μm, solving the problem of tool sticking; stable cutting performance.

[0047] If Al>0.5% or Zr>0.8%, the elongation will be less than 23%, the cutting force will be greater than 500 N, and the economic efficiency will be significantly reduced. Strength gain must be at the expense of plasticity or processing efficiency (such as A3Z3 cutting force 520 N vs A2Z2 480N).

[0048] A preparation method of a Ti-Zr-Al alloy, characterized in that the target composition range of the Ti-Zr-Al alloy is Al: 0.1-0.5%; Zr: 0.4-0.8%; Fe: 0.30-0.40%; O: 0.30-0.40%; C: <0.08; N: <0.05; H: <0.015; the ratio of each alloy element is determined according to the target composition range, and the alloy raw material to be added is determined; sponge titanium and alloy raw material are weighed, and the sponge titanium and alloy raw material are evenly mixed to form a raw material to be pressed 15; The raw material 15 to be pressed is pressed into an electrode block 1, and a plurality of the electrode blocks 1 are stacked into a consumable electrode 2 to be welded; the consumable electrode 2 is welded, and the consumable electrode 2 is smelted in a vacuum consumable arc furnace to prepare a Ti-Zr-Al alloy.

[0049] The present invention adds 0.10-0.50 Al and 0.40-0.80 Zr elements to the titanium alloy to improve the strength of the alloy and improve some processing properties. By accurately proportioning the elements in the titanium alloy, the composition ratio meets the composition requirements of the titanium alloy, effectively controls the content of impurity elements in the Ti-Zr-Al titanium alloy ingot, and ensures the quality of the titanium alloy ingot.

[0050] Further, the raw material 15 to be pressed is pressed into an electrode block 1, such as Figure 2 As shown, the step of stacking a plurality of the electrode blocks 1 into a consumable electrode 2 to be welded comprises: The raw material 15 to be pressed is pressed into an electrode block 1 by an arc-shaped punch 13 of a hydraulic press, one of the two sides of the electrode block 1 is an arc surface 5, and the other side of the two sides of the electrode block 1 is a plane; the planes of two electrode blocks 1 are fitted together to form a section of the consumable electrode 2, and multiple sections of the consumable electrodes 2 are stacked into a consumable electrode 2 to be welded; the height of the cross section of the electrode block 1 is 225-290 mm, the width of the cross section of the electrode block 1 is 420-540 mm, and the diagonal length of the cross section of the consumable electrode 2 is 480-620 mm.

[0051] like Figure 1 , 2 As shown, when the hydraulic press presses the electrode block 1, the punch 13 of the hydraulic press squeezes the raw material 15 to be pressed in the die 14. Since the punch 13 is in an arc shape, as the punch 13 continuously squeezes the raw material 15 to be pressed, the powder particles in the raw material 15 to be pressed have good overall fluidity, a small displacement shear area, and the surface cracks of the electrode block 1 are effectively eliminated. The compressed side of the raw material 15 to be pressed forms the arc surface 5 of the electrode block 1, and the other side is squeezed with the bottom 7 of the die 14 to form a flat surface.

[0052] Furthermore, the step of welding with the consumable electrode 2 includes: The consumable electrode 2 is welded by an electron beam welding box, or the consumable electrode 2 is welded by a plasma welding box; the electron beam welding box or the plasma welding box is provided with a plurality of welding guns, the plurality of welding guns are arranged at intervals along the length direction of the consumable electrode 2, the distance between adjacent welding guns is L, the length of a section of the consumable electrode 2 is L1, L=L1*n, n is a positive integer, and the plurality of welding guns weld the gaps between the sections of the consumable electrode 2 to form a transverse weld 4. In this way, the plurality of welding guns can correspond to the gaps between the plurality of sections of the consumable electrode 2 one by one, and the plurality of gaps can be automatically welded at the same time, thereby improving the welding efficiency.

[0053] Further, the step of welding the consumable electrode 2 by an electron beam welding box or welding the consumable electrode 2 by a plasma welding box includes: The consumable electrode 2 is welded along the length direction of the consumable electrode 2 by the electron beam welding box or the plasma welding box to form a longitudinal weld 3, and a plurality of the longitudinal welds 3 are arranged at intervals. The longitudinal welds 3 are arranged to enhance the connection strength between the electrode blocks 1 and avoid the block falling during the smelting process.

[0054] Further, when the consumable electrode 2 is welded by the electron beam welding box, the welding current is 2A-3A and the welding voltage is 20KV-25KV. When the electron beam welding box is used for welding, the energy density is very high, the electron beam can be focused to a very small diameter, and a large amount of heat can be generated in a very small area. For the welding of the consumable electrode 2, this high energy density can achieve high-precision welding, which can make the weld very narrow and have a large aspect ratio. For example, when welding some consumable electrodes 2 with high dimensional accuracy requirements, excessive material melting can be avoided, reducing the impact on the original shape and size of the electrode.

[0055] At a voltage of 20KV-25KV and a current of 2A-3A, the electron beam can quickly melt and solidify the metal. Since the electron beam has concentrated energy, the heat input is relatively concentrated and efficient, and the welding process can be completed in a short time. This helps to improve production efficiency and can greatly shorten the welding time.

[0056] Electron beam welding produces a very small heat affected zone. Because the heat is mainly concentrated in the area where the electron beam is focused, the thermal impact on the surrounding material is small. For the consumable electrode 2, this means that the rest of the electrode is less affected by heat during welding, which can reduce thermal deformation and thermal stress, and prevent the electrode from cracking due to thermal stress after welding.

[0057] Furthermore, when the consumable electrode 2 is welded by the plasma welding box, the welding current is 400A-600A, and the welding voltage is 60V-90V.

[0058] When plasma welding uses a welding current of 400A-600A and a welding voltage of 60V-90V, it can generate a large arc energy. This higher energy can make the weld obtain a larger penetration and a relatively wider weld. For some consumable electrodes 2 with large sizes or high requirements for weld strength, plasma welding can ensure that the weld has sufficient fusion depth and width, and improve the overall strength and connection reliability of the electrode.

[0059] Compared with electron beam welding, plasma arc has better stability and stiffness, and has relatively low requirements for the assembly accuracy of the consumable electrode 2. During the welding process, even if the butt gap of the consumable electrode 2 has a certain deviation, the plasma arc can well fill the gap and form a weld of qualified quality, and the requirements for the fixture of the consumable electrode 2 are relatively low.

[0060] In addition, the cost and maintenance difficulty of plasma welding box are lower than that of electron beam welding box.

[0061] Furthermore, the step of determining the ratio of each alloy element according to the target composition range of the Ti-Zr-Al alloy includes: determining the ratio of each alloy element according to the target composition range of the Ti-Zr-Al alloy as Al: 0.3%, Zr: 0.6%; Fe: 0.35%; O: 0.30%. Considering the element segregation, the target value of Fe is set to 0.35%, and the target value of Zr is set to 0.6%; considering the increase in oxygen during the smelting process, the target value of O is set to 0.30%; considering the large amount of Al volatilization during the VAR smelting process, the target value of Al is set to 0.30%.

[0062] Further, the step of melting the consumable electrode 2 by a vacuum consumable arc furnace includes: the diagonal length of the cross section of the consumable electrode 2 is 480 mm, the consumable electrode 2 is melted by a crucible with a diameter of 580 mm to prepare a primary ingot, the melting current is 14-18KA, and the melting voltage is 30-35V; the primary ingot is melted by a crucible with a diameter of 650 mm to prepare a secondary ingot, the melting current is 20-24KA, and the melting voltage is 30-35V; the secondary ingot is melted by a crucible with a diameter of 720 mm to prepare a Ti-Zr-Al alloy, the melting current is 25-29KA, and the melting voltage is 30-35V. The three meltings make the components of each alloy element uniform and the segregation degree low.

[0063] Furthermore, the step of determining the alloy raw materials to be added includes: adding Al element in the form of aluminum beans; adding Zr element in the form of zirconium sponge; adding Fe element in the form of titanium-iron alloy or iron nails; and adding O element in the form of titanium dioxide.

[0064] Aluminum beans are a relatively cheap and easy to handle form. Compared with other forms such as aluminum powder, aluminum beans have a lower cost. By adding the Fe element in the form of ferrotitanium alloy, the uniformity of the Fe element in the ingot can be improved. Since the procurement cost of iron nails is lower than that of ferrotitanium alloy, the raw material procurement cost can be reduced by adding the Fe element in the form of iron nails. It should be noted that the iron nails are iron nails with a diameter of less than 3 mm and a length of less than 20 mm, so as to improve the uniformity of the Fe element in the ingot on the basis of reducing the raw material procurement cost.

[0065] Further, the step of weighing the titanium sponge and the alloy raw material, and uniformly mixing the titanium sponge and the alloy raw material to form the raw material to be pressed 15 includes: The titanium sponge and the alloy raw material are weighed by an automatic mixer, and the titanium sponge and the alloy raw material are mixed evenly by a mixer to form a raw material to be pressed 15, the mixing time of the mixer is 30-90S, and the weight of the raw material to be pressed 15 is 140-200kg. The weighing is accurate and efficient by the automatic mixer. By setting the mixing time to 30-90S and the weight of the raw material to be pressed 15 to 140-200kg, it is ensured that the titanium sponge and the alloy raw materials in the raw material to be pressed 15 are mixed evenly.

[0066] Specifically, a crucible with a size of 580mm in diameter × height and a bottom pad is assembled and loaded into a smelting station, and then the consumable electrode 2 is loaded into the crucible and fixed, and the furnace is sealed and evacuated; the consumable electrode 2 after evacuation is welded with the auxiliary electrode in a vacuum consumable arc furnace, and the vacuum degree before welding is controlled not to exceed 10Pa, and the welding current is 2kA-15kA. After welding, the consumable electrode 2 connected to the auxiliary electrode is obtained, and after cooling for more than 40 minutes, it is taken out of the furnace for inspection to ensure the connection strength between the consumable electrode 2 and the auxiliary electrode; the furnace is sealed and evacuated again, and the vacuum degree before melting is controlled not to exceed 5Pa, and the leakage rate is not more than 0.6Pa / min, and then power is supplied to start an arc for one smelting to obtain an ingot; the smelting current of the one smelting is 14-18KA, and the smelting voltage is 30-35V.

[0067] The primary ingot is cleaned by an ingot washer to remove surface impurities. The primary ingot is machined flat on a lathe until the flash does not exceed 5 mm. A crucible with a diameter × height of 650 mm × 4800 mm is assembled with a bottom pad and loaded into the smelting station. The bottom 7 and the head 6 of the primary smelting ingot are reversed and placed in the crucible as the consumable electrode 2 for the secondary smelting.

[0068] The bottom 7 of the primary ingot is welded with the auxiliary electrode in a vacuum consumable arc furnace, the vacuum degree before melting is controlled not to exceed 10Pa, the welding current is 2kA-15kA, and the primary ingot connected with the auxiliary electrode is obtained after welding. After cooling for more than 60min, the ingot is taken out of the furnace for inspection to ensure the connection strength between the primary ingot and the auxiliary electrode; the furnace is sealed and vacuumed again, the vacuum degree before melting is controlled not to exceed 5Pa, and the gas leakage rate is not more than 0.6Pa / min, and then power is supplied to start the arc for secondary smelting to obtain a secondary ingot; the smelting current of the secondary smelting is 20-24KA, and the smelting voltage is 30-35V; A crucible with a size of 720mm in diameter × height and a bottom pad is assembled and loaded into a smelting station. The bottom 7 and the head 6 of the secondary smelting ingot are reversed and put into the crucible as the consumable electrode 2 for the tertiary smelting. The bottom 7 of the secondary ingot is welded with the auxiliary electrode in a vacuum consumable arc furnace. The vacuum degree before melting is controlled not to exceed 10Pa, and the welding current is 2kA-15kA. After welding, a secondary ingot connected to the auxiliary electrode is obtained. After cooling for more than 60 minutes, it is taken out of the furnace for inspection to ensure the connection strength between the secondary ingot and the auxiliary electrode; the furnace is re-sealed and evacuated, and the vacuum degree before melting is controlled not to exceed 1.33Pa, and the leakage rate is not more than 0.6Pa / min. Then, power is supplied to start the arc for tertiary smelting, and shrinkage is supplemented in the later stage of smelting to obtain a titanium alloy ingot; the tertiary ingot melting current is 25-29KA, and the smelting voltage is 30-35V; and finally a finished ingot with a diameter of 700±10mm is obtained.

[0069] During the secondary and tertiary smelting, the bottom 7 and the head 6 of the ingot from the previous smelting are reversed to serve as the next consumable electrode 2. According to production practice, if the ingot is always placed upright as the consumable electrode 2 during the three smeltings, the macro segregation of the ingot is the heaviest; if the ingot is reversed as the consumable electrode 2 at least once, the axial macro segregation of the ingot can be significantly reduced.

[0070] In addition, during the titanium alloy vacuum consumable arc melting (VAR melting), a set gap needs to be maintained between the consumable electrode 2 and the crystallizer 8. The adjustment and maintenance of this gap is of great significance to the titanium alloy vacuum consumable arc melting. Maintaining an appropriate gap between the consumable electrode 2 and the crystallizer 8 helps to ensure the smooth progress of the melting process; the size of the gap can affect the melting rate of the consumable electrode 2; an appropriate gap helps to control the melting rate of the electrode, thereby controlling the solidification process of the ingot; maintaining the gap between the consumable electrode 2 and the crystallizer 8 helps to uniformly cool the ingot. By adjusting the gap, it can ensure that the ingot is cooled uniformly all around, avoiding internal stress and cracks caused by uneven cooling; uniform cooling and appropriate gaps help to improve the quality of the ingot, reduce defects, and improve the mechanical and physical properties of the product.

[0071] Therefore, when the consumable electrode 2 is melted in the VAR furnace, a positioning device for the consumable electrode 2 is used. The positioning device includes a plurality of wedges 9. The plurality of wedges 9 are evenly placed between the top edge of the consumable electrode 2 and the body of the crystallizer 8. Figure 5As shown; the wedge 9 is a triangular prism structure, and the wedge 9 includes a bottom plate 10, a first side plate 11 and a second side plate 12. The angle between the bottom plate 10 and the first side plate 11 is a, and the angle between the bottom plate 10 and the second side plate 12 is b. The material of the bottom plate 10, the first side plate 11 and the second side plate 12 is the same as the alloy material for vacuum consumable arc melting, and one end of the wedge 9 at the angle b is inserted into the gap between the consumable electrode 2 and the cylinder of the crystallizer 8.

[0072] A plurality of wedges 9 are evenly placed between the top edge of the consumable electrode 2 and the cylinder of the crystallizer 8, and one end of each wedge 9 at an angle b is inserted into the gap between the consumable electrode 2 and the cylinder of the crystallizer 8. By adjusting the position of the consumable electrode 2, the plurality of wedges 9 are at the same horizontal height, so that the gap between the consumable electrode 2 and the crystallizer 8 is uniform. The consumable electrode 2 is located at the center of the crystallizer 8. Since the material of the first side plate 11 and the second side plate 12 of the bottom plate 10 is the same as the alloy material for vacuum consumable arc melting, it is avoided that foreign matter is brought into the crystallizer 8 during the furnace loading process to pollute the melting. Since the material is an alloy, the structural strength is improved, and the positioning device can avoid deformation that causes uneven gap between the consumable electrode 2 and the crystallizer 8, affecting melting safety and ingot quality. It is also avoided that during the welding process of the consumable electrode 2 and the auxiliary electrode, the positioning device is self-ignited at high temperature, resulting in increased air pressure in the crystallizer 8, affecting welding safety.

[0073] The welding current range is 100A-250A, the welding voltage range is 12V-18V, and the welding speed range is 8mm / s-15mm / s, ensuring the welding strength and the overall structural performance of the wedge 9 Specifically, the wedge 9 also includes two ribs 21, and the two ribs 21 are symmetrically arranged on both sides of the bottom plate 10; the ribs 21 are triangular, and the three sides of the ribs 21 are respectively connected to the bottom plate 10, the first side plate 11 and the second side plate 12. Considering that the wedge 9 with a closed structure cannot be formed by the bottom plate 10, the first side plate 11 and the second side plate 12 alone, ribs 21 are welded on both sides thereof, so that the wedge 9 has a closed structure as a whole, thereby improving the overall strength of the wedge 9.

[0074] Specifically, the ribs 21 are provided with scale lines 22 with marking functions in the vertical direction; the scale lines 22 are used to observe the insertion depth of the wedges 9. When the scale lines on the bottom plates 10 of the multiple wedges 9 are at the same vertical distance from the top edge of the consumable electrode 2, it means that the multiple wedges 9 are at the same horizontal height, thereby achieving the purpose of improving positioning accuracy.

[0075] Specifically, the scale lines 22 are scale lines formed by laser etching, chemical etching or mechanical engraving. Since the scale lines 22 are formed by laser etching, chemical etching or mechanical engraving, the clarity and wear resistance of the scale lines are improved, and the wedge 9 is not easy to wear or display blur during use.

[0076] Specifically, the corners of the wedge 9 are chamfered; in order to prevent the wedge 9 from causing scratches to the operator during use, and to reduce the scratches on the surface of the consumable electrode 2 and the crystallizer 8 during the insertion and adjustment of the wedge 9, chamfers are set at the corners of the wedge 9, and the chamfer radius ranges from 0.5mm to 3mm.

[0077] Specifically, the bottom plate 10 , the first side plate 11 and the second side plate 12 are all provided with weight-reducing holes 23 ; in order to reduce the weight of the wedge 9 itself, a plurality of weight-reducing holes 23 are provided thereon.

[0078] Specifically, the bottom plate 10 of the wedge 9 is 200-300 mm long, the width of the side where the bottom plate 10 is connected to the first side plate 11 is 80-150 mm, and the thickness is 80-150 mm. Preferably, the angle a between the bottom plate 10 and the first side plate 11 is in the range of 90°-150°, and the angle b between the bottom plate 10 and the second side plate 12 is in the range of 15°-45°.

[0079] The bottom plate 10, the first side plate 11 and the second side plate 12 are integrally formed. Preferably, the bottom plate 10, the first side plate 11 and the second side plate 12 are all titanium alloy plates from scrap materials, and the bottom plate 10, the first side plate 11 and the second side plate 12 are connected by welding. Considering that there are many specifications of the crystallizer 8 and the consumable electrode 2, and the sizes of different specifications are also different, in order to ensure that the wedge 9 can be effectively used, the size of the wedge 9 and the angle a and angle b are also various, so that the staff can select a suitable wedge 9 according to the specifications of the crystallizer 8 and the consumable electrode 2. At the same time, the raw material of the wedge 9 is mainly taken from the titanium alloy plate in the scrap material, and it is properly processed according to the size of the titanium alloy plate itself to make it a wedge 9 that meets the above requirements.

[0080] The working principle of the positioning device for the consumable electrode 2 provided in the present application is as follows: S1: The consumable electrode 2 is hoisted onto the bottom pad of the crystallizer 8, and then the cylinder of the crystallizer 8 is covered on the outside of the consumable electrode 2 by a crane, and the crystallizer 8 and the bottom pad are tightened and fixed by bolts.

[0081] S2: Multiple wedges 9 are evenly placed between the top edge of the consumable electrode 2 and the cylinder of the crystallizer 8, and the multiple wedges 9 are symmetrically arranged. That is, one end of the angle b is inserted downward into the gap between the consumable electrode 2 and the cylinder of the crystallizer 8, the first side plate 11 is higher than the top edge of the consumable electrode 2, and the bottom plate 10 is in contact with the inner side of the crucible. The larger the gap between the consumable electrode 2 and the cylinder of the crystallizer 8, the lower the horizontal height of the first side plate 11. When the wedge 9 is at the minimum height, the wedge 9 is flush with the top edge of the consumable electrode 2. For example, four wedges 9 are placed every 90° along the inner circle of the crucible, and the position of the consumable electrode 2 is adjusted so that the four wedges 9 are at the same horizontal height, so that the gap between the consumable electrode 2 and the crystallizer 8 is uniform, and the consumable electrode 2 is located at the center of the bottom pad of the crystallizer 8.

[0082] The specific applications of the positioning device are as follows: When the diameter of the crucible is 580 mm and the diameter of the consumable electrode 2 is 480 mm, the wedge 9 is used to make the gap between the consumable electrode 2 and the crystallizer 8 at all locations 50 mm; When the diameter of the crucible is 650 mm and the diameter of the consumable electrode 2 is 570 mm, the wedge 9 is used to make the gap between the consumable electrode 2 and the crystallizer 8 at all locations 40 mm; When the diameter of the crucible is 720 mm and the diameter of the consumable electrode 2 is 640 mm, the wedge 9 is used to ensure that the gap between the consumable electrode 2 and the crystallizer 8 at all locations is 40 mm.

[0083] The specific embodiments of the present invention are described below: Embodiment 1: Step 1: The ingredients of the target ingot product are as follows (weight percentage): Fe: 0.30-0.40; C: <0.08; N: <0.05; H: <0.015; O: 0.30-0.40; Al: 0.10-0.50; Zr: 0.40-0.8.

[0084] Select zirconium sponge, titanium-iron alloy or iron nails, titanium dioxide, aluminum beans and titanium sponge as raw materials, and determine the amount of each raw material according to the target composition and specifications of the ingot.

[0085] Specifically, taking into account the element segregation, the target value of Fe is set to 0.35%, and the target value of Zr is set to 0.65%; taking into account the oxygen increase phenomenon during the smelting process, the target value of O is set to 0.30%; taking into account the large amount of Al volatilization during the VAR smelting process, the target value of Al is set to 0.30%, and the total weight of the ingot is 6159.400 kg.

[0086] The specific target ingredients are as follows: Fe: 0.35% C: <0.08% N: <0.05% H: <0.015% O: 0.30% Al: 0.3% Zr: 0.65% Specific raw materials and their purity: Zirconium sponge: 99% Zr; Ferro-titanium alloy: 65% Ti, the rest is mainly Fe; Titanium dioxide: 47.9% Ti, 52.1% O; Aluminum beans: 99% Al; Titanium sponge: 99% Ti; The required amount of raw materials calculated according to the batching target is as follows: The amount of Zr required: 37.973 kg of 99% pure sponge zirconium is required; The amount of Al required: 18.505 kg of 99% pure aluminum beans are needed; The amount of TiO2 required is 41.310 kg; Required amount of titanium iron alloy: 61.613kg; 6000kg of titanium sponge was used and the total weight of the ingot was 6159.400kg.

[0087] Step 2: The electrode block is prepared by using an automatic mixer to weigh different raw materials and mix them evenly; an 8000-ton hydraulic press is used to press the evenly mixed raw materials to prepare an electrode block. For example, the size of the electrode block is 480×420×225, the density is 3.4-3.5g / cm3, and the unit weight is 100kg-140kg; the shape of the electrode block can be square or semicircular with a diameter of 480mm, and one side of the square can also be set as an arc surface. The cross-sectional shape of the electrode block pressed in this embodiment is as follows: Figure 1 shown.

[0088] Step 3: Stack the electrode blocks into consumable electrodes. For example, there are two electrode blocks in each section, and the materials are stacked along the length direction, with a total of 11 sections. The total length of the consumable electrode is 5-6m. Welding is performed by electron beam welding box, welding methods such as Figure 1 , 3 As shown, the welding current is 2A-3A, the welding voltage is 20KV-25KV; or welding is performed through a plasma welding box, the welding method is as follows Figure 1 , 3 As shown, the welding current is 400A-600A and the welding voltage is 60V-90V.

[0089] Multiple electron beam welding guns or plasma welding guns can be set, the horizontal distance between the multiple welding guns is L, the distance between the horizontal connections of the multiple electrode blocks is L1, L=L1×n, n is a positive integer, so that the multiple welding guns can correspond one-to-one to the horizontal connections of the multiple electrode blocks, and automatically weld the multiple connections at the same time. The schematic diagram of the consumable electrode shown in this embodiment is shown in Figures 1 and 3.

[0090] Step 4: The crucible with a diameter of 580 is used for primary melting, the melting current is 14-18KA, and the melting voltage is 30-35V; Secondary melting is carried out in a crucible with a diameter of 650, with a melting current of 20-24KA and a melting voltage of 30-35V; The crucible with a diameter of 720 is used for three smelting, the smelting current is 25-29KA, and the smelting voltage is 30-35V; Finally, a finished ingot with a diameter of 700±10 mm is obtained.

[0091] Two ingots were prepared by the above steps, and samples were taken after peeling. The sampling positions on the ingots were as follows: Figure 4 As shown, the ingot composition was tested, and the test results are shown in Table 4 below. After testing, the target range requirements were met.

[0092] Table 4 Ingot 1 composition test results

[0093] Embodiment 2: Step 1: The ingredients of the target ingot product are as follows (weight percentage): Fe: 0.30-0.40; C: <0.08; N: <0.05; H: <0.015; O: 0.30-0.40; Al: 0.10-0.50; Zr: 0.4-0.8.

[0094] Select zirconium sponge, titanium-iron alloy or iron nails, titanium dioxide, aluminum beans and titanium sponge as raw materials, and determine the amount of each raw material according to the target composition and specifications of the ingot.

[0095] Specifically, taking into account the element segregation, the target value of Fe is set to 0.35%, and the target value of Zr is set to 0.60%; taking into account the oxygen increase phenomenon during the smelting process, the target value of O is set to 0.30%; taking into account the large amount of Al volatilization during the VAR smelting process, the target value of Al is set to 0.30%, and the total weight of the ingot is 6158.867 kg.

[0096] The specific target ingredients are as follows: Fe: 0.35% C: <0.08% N: <0.05% H: <0.015% O: 0.30% Al: 0.30% Zr: 0.60% Specific raw materials and their purity: Zirconium sponge: 99% Zr; Ferro-titanium alloy: 65% Ti, the rest is mainly Fe; Titanium dioxide: 47.9% Ti, 52.1% O; Aluminum beans: 99% Al; Titanium sponge: 99% Ti; The required amount of raw materials calculated according to the batching target is as follows: The amount of Zr required: 37.970 kg of 99% pure sponge zirconium is required; The amount of Al required: 18.503 kg of aluminum beans with 99% purity are needed; The amount of TiO2 required is 40.164 kg; Required amount of titanium iron alloy: 62.230kg; 6000kg of titanium sponge was used; the total weight of the ingot was 6158.867kg.

[0097] Step 2: For the preparation of electrode blocks, different raw materials are weighed separately by an automatic mixer and mixed evenly; the evenly mixed raw materials are pressed by an 8000-ton hydraulic press to prepare electrode blocks. For example, the electrode blocks have a size of 480×420×225, a density of 3.4-3.5g / cm3, and a unit weight of 100kg-140kg; the shape of the electrode blocks can be square or semicircular with a diameter of 480mm, and one side of the square can also be set as an arc surface.

[0098] Step 3: The electrode blocks are stacked into consumable electrodes. For example, each section of the electrode block has two blocks, and the material is stacked along the length direction, with a total of 11 sections. The total length of the consumable electrode is 5-6m.

[0099] Welding is performed by electron beam welding box, with a welding current of 2A-3A and a welding voltage of 20KV-25KV; or welding is performed by plasma welding box, with a welding current of 400A-600A and a welding voltage of 60V-90V.

[0100] Multiple electron beam welding guns or plasma welding guns can be provided, the horizontal distance between the multiple welding guns is L, the distance between the horizontal connections of the multiple electrode blocks is L1, L=L1×n, n is a positive integer, so that the multiple welding guns can correspond to the horizontal connections of the multiple electrode blocks one by one, and the multiple connections can be automatically welded at the same time. The schematic diagram of the consumable electrode shown in this embodiment is as follows Figure 1 , 3 shown.

[0101] Step 4: The crucible with a diameter of 580 is used for primary melting, the melting current is 14-18KA, and the melting voltage is 30-35V; Secondary melting is carried out in a crucible with a diameter of 650, with a melting current of 20-24KA and a melting voltage of 30-35V; The crucible with a diameter of 720 is used for three smelting, the smelting current is 25-29KA, and the smelting voltage is 30-35V; Finally, a finished ingot with a diameter of 700±10 mm is obtained.

[0102] Two ingots were prepared by the above steps, and samples were taken after peeling. The sampling positions on the ingots were as follows: Figure 4 As shown, the ingot composition was tested, and the test results are shown in Table 5 below. After testing, the target range requirements were met.

[0103] Table 5 Ingot 2 composition test results

[0104] By selecting reasonable element composition batching, reasonable intermediate alloy, reasonable consumable electrode size, reasonable smelting parameters and smelting times, a titanium alloy ingot containing aluminum and zirconium elements with a total weight of 3000-6000kg is prepared. The ingot has good composition uniformity after testing.

[0105] As an improvement to reduce the segregation of ingot elements, specifically: electromagnetic stirring is used in the VAR smelting process to enhance melt convection and promote uniform distribution of alloy elements. The electromagnetic stirring includes an electromagnetic induction coil arranged outside the water jacket, the coil is connected to a power supply, and is provided with a sensor and a controller to monitor and adjust the magnetic field strength and direction. The characteristics of the magnetic field are controlled by adjusting the current size and direction to move the metal liquid in the titanium alloy molten pool.

[0106] Setting of electromagnetic stirring structure: one or more sets of electromagnetic coils are installed around the outside of the smelting water jacket. An adjustable current source is equipped as a power control system, which can change the current size and direction, thereby adjusting the direction and intensity of the magnetic field. The electromagnetic stirring system should have a fast response capability to accurately control the stirring effect.

[0107] When current is passed through the arc stabilizing coil, a longitudinal field is generated in the coil. When the charged particles in the arc cross the magnetic field, they are acted upon by the magnetic force (i.e., the Lorentz force), which prevents them from crossing and makes them move along the direction of the magnetic field. This ensures that the arc is not strayed, thus achieving the purpose of arc stability. Similarly, since the current in the molten pool crosses the longitudinal magnetic field, it is also acted upon by the magnetic force. The direction of the magnetic force is to rotate the current-carrying molten metal, thus playing the role of stirring the molten pool.

[0108] High-temperature-resistant and high-strength copper alloy or silver-copper alloy is used to ensure that the coil can withstand high temperatures and maintain good conductivity when energized. The cooling system uses forced water cooling to ensure that the coil temperature does not exceed the safe working range. Temperature sensors, position sensors and other equipment are installed to monitor the status of the molten pool and feed back information to the control system to achieve automated operation.

[0109] During the smelting process, the parameters of the smelting process are guided by monitoring the magnetic field of the electromagnetic stirring. The specific relationship between the electromagnetic field intensity and the smelting current includes the following: 1. Electromagnetic field strength and melt convection: Strong magnetic field: If the monitored electromagnetic field strength is higher than expected, this may mean that the stirring effect is too strong, which may cause excessive turbulence in the melt, affect the uniformity of the composition and increase the risk of pore formation. At this time, you should consider reducing the melting current or changing the frequency to weaken the stirring effect.

[0110] Weak magnetic field: On the contrary, if the electromagnetic field strength is insufficient, the melt convection is insufficient and cannot effectively promote the mixing of components and the floating of inclusions. At this time, the stirring force can be enhanced by appropriately increasing the melting current or adjusting the frequency.

[0111] 2. Electromagnetic field strength and melting rate: The melting current directly affects the energy input of the arc, which in turn affects the melting rate. High current can speed up the melting speed; the strengthening of electromagnetic stirring current can form a stronger electromagnetic effect. Therefore, it is necessary to find a balance point to make the electromagnetic stirring current compatible with the melting, provide a sufficient melting rate, and a suitable electromagnetic field.

[0112] 3. Electromagnetic field strength and temperature distribution: Appropriate electromagnetic stirring helps to homogenize the temperature distribution of the molten pool. If abnormal electromagnetic field strength is detected in certain areas (such as locally too strong or too weak), the melting current can be fine-tuned.

[0113] Specific adjustment examples: For example, in a VAR melting process, real-time monitoring shows that the electromagnetic field intensity is too high, resulting in violent fluctuations on the melt surface, which may be caused by excessive stirring current. At this time, the following measures can be taken: Reduce stirring current: Gradually reduce the current until the melt surface fluctuation is observed to return to normal, while paying close attention to changes in the melting rate to ensure that it still meets production needs.

[0114] Stirring cycle: If reducing the current is not enough to solve the problem, you can also adjust the stirring cycle. By adjusting the direction of the current, you can control the forward or reverse stirring of the molten metal in the molten pool. The stirring cycle determines the flow state of the molten metal in the molten pool. The flow state in the molten pool can affect the mixing uniformity of the melt and the solidification process.

[0115] Optimize cooling conditions: In conjunction with the above adjustments, check that the cooling system is working properly to ensure that the ingot cooling rate is appropriate to avoid internal stress and cracks caused by rapid cooling.

[0116] On the basis of real-time monitoring of electromagnetic field intensity, by precisely controlling other key parameters such as the magnitude and direction of the stirring current, more precise quality control can be achieved during the smelting process, thereby improving the quality and consistency of titanium alloy ingots. This real-time adjustment not only relies on process monitoring technology and automated control systems, but also requires technical accumulation and practical experience support.

[0117] Electromagnetic stirring control: Electromagnetic stirring is used during the smelting process to improve the fluidity of the alloy liquid and promote the homogenization of the composition. It should be noted that the stirring intensity should be carefully controlled in the early and late stages of smelting to avoid composition segregation or inclusion problems caused by excessive stirring. In addition, in order to adapt to the new composition range, especially in controlling the oxygen (O) and nitrogen (N) content, the stirring intensity can be appropriately reduced at the end of smelting to help remove gas and reduce oxide inclusions.

[0118] Initial start-up: Soon after smelting begins, when the molten pool is initially formed but not yet completely melted, start the electromagnetic stirring system.

[0119] Stabilization period: As the smelting process progresses, the current intensity is gradually increased to generate sufficient eddy current movement inside the molten pool to promote uniform distribution of alloy elements.

[0120] Late adjustment: Before the end of smelting, appropriately reducing the current intensity and reducing the stirring intensity will help form a denser organizational structure and prevent component segregation caused by excessive stirring.

[0121] Parameter setting: During the whole process, the melting current is 14-18KA (primary ingot), 20-24KA (secondary ingot), 25-29KA (final alloy), and the melting voltage is kept in the range of 30-35V. The current direction and intensity of electromagnetic stirring can be flexibly adjusted according to the actual conditions of the molten pool to achieve the best stirring effect. The introduction of electromagnetic and controlled stirring technology in the VAR melting process of Ti-Zr-Al alloy ingots significantly improves the composition uniformity in the molten pool and the quality of the ingots. This method not only improves the melting efficiency, but also provides a strong guarantee for obtaining high-performance titanium alloy ingots.

[0122] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A Ti-Zr-Al alloy, characterized in that: The following ingredients are included in percentage by weight: 0.1-0.5% aluminum; 0.4-0.8% zirconium; 0.30-0.40% iron; 0.30-0.40% oxygen; 0-0.08% carbon; 0-0.05% nitrogen; 0-0.015% hydrogen; The remainder consists of titanium and unavoidable impurities.

2. A method for preparing a Ti-Zr-Al alloy, characterized in that: Determine the ratio of each alloy element according to the target composition range, and determine the alloy raw material to be added; weigh the titanium sponge and the alloy raw material, and mix the titanium sponge and the alloy raw material evenly to form a raw material to be pressed; Pressing the raw material to be pressed into an electrode block, and stacking a plurality of the electrode blocks into a consumable electrode to be welded; The consumable electrode is welded and smelted in a vacuum consumable arc furnace to prepare a Ti-Zr-Al alloy.

3. The method for preparing a Ti-Zr-Al alloy according to claim 2, characterized in that: The step of pressing the raw material to be pressed into an electrode block, and stacking a plurality of the electrode blocks into a consumable electrode to be welded comprises: The raw material to be pressed is pressed into an electrode block by an arc-shaped punch of a hydraulic press, one of the two sides of the electrode block is an arc surface, and the other side of the two sides of the electrode block is a plane; the planes of two electrode blocks are fitted together to form a section of the consumable electrode, and multiple sections of the consumable electrodes are stacked into a consumable electrode to be welded; the height of the cross section of the electrode block is 225-290mm, the width of the cross section of the electrode block is 420-540mm, and the diagonal length of the cross section of the consumable electrode is 480-620mm.

4. The method for preparing a Ti-Zr-Al alloy according to claim 3, characterized in that: The steps of welding with the consumable electrode include: The consumable electrode is welded by an electron beam welding box, or the consumable electrode is welded by a plasma welding box; the electron beam welding box or the plasma welding box is provided with a plurality of welding guns, the plurality of welding guns are arranged at intervals along the length direction of the consumable electrode, the distance between adjacent welding guns is L, the length of a section of the consumable electrode is L1, L=L1*n, n is a positive integer, and the plurality of welding guns weld the gaps between the sections of the consumable electrode to form a transverse weld.

5. The method for preparing a Ti-Zr-Al alloy according to claim 4, characterized in that: The step of welding the consumable electrode by an electron beam welding box or welding the consumable electrode by a plasma welding box comprises: The consumable electrode is welded along the length direction of the consumable electrode by the electron beam welding box or the plasma welding box to form a longitudinal weld, and a plurality of the longitudinal welds are arranged at intervals.

6. A method for preparing a Ti-Zr-Al alloy according to any one of claims 2 to 5, characterized in that: The step of determining the proportion of each alloy element according to the target composition range of the Ti-Zr-Al alloy includes: determining the proportion of each alloy element according to the target composition range of the Ti-Zr-Al alloy as Al: 0.3%, Zr: 0.6%; Fe: 0.35%; O: 0.30%.

7. A method for preparing a Ti-Zr-Al alloy according to any one of claims 3 to 5, characterized in that: The step of melting the consumable electrode by a vacuum consumable arc furnace comprises: the outer diameter of the consumable electrode cross section is 480 mm, the consumable electrode is melted once by a crucible with a diameter of 580 mm to prepare a primary ingot, the melting current is 14-18KA, and the melting voltage is 30-35V; the primary ingot is melted twice by a crucible with a diameter of 650 mm to prepare a secondary ingot, the melting current is 20-24KA, and the melting voltage is 30-35V; the secondary ingot is melted three times by a crucible with a diameter of 720 mm to prepare a Ti-Zr-Al alloy, the melting current is 25-29KA, and the melting voltage is 30-35V; at least one of the three meltings is in the form of inverting the bottom and the head of the ingot as the consumable electrode for the next melting.

8. A method for preparing a Ti-Zr-Al alloy according to any one of claims 2 to 5, characterized in that: The step of determining the alloy raw materials to be added includes: adding Al element in the form of aluminum beans; adding Zr element in the form of zirconium sponge; adding Fe element in the form of titanium-iron alloy or iron nails; and adding O element in the form of titanium dioxide.

9. The method for preparing a Ti-Zr-Al alloy according to any one of claims 2 to 5, characterized in that: The step of weighing the titanium sponge and the alloy raw material, and uniformly mixing the titanium sponge and the alloy raw material to form a raw material to be pressed comprises: The titanium sponge and the alloy raw material are weighed by an automatic mixer, and the titanium sponge and the alloy raw material are evenly mixed by a mixer to form a raw material to be pressed. The mixing time of the mixer is 30-90S, and the weight of the raw material to be pressed is 140-200kg.

10. A method for preparing a Ti-Zr-Al alloy according to any one of claims 2 to 5, characterized in that: Electromagnetic stirring is used in the VAR smelting process to enhance melt convection and promote uniform distribution of alloy elements. The electromagnetic stirring includes an electromagnetic induction coil arranged outside the water jacket. The coil is connected to a power supply, and the magnetic field strength and direction are monitored and adjusted through sensors and controllers. The characteristics of the magnetic field are controlled by adjusting the current size and direction to make the metal liquid in the titanium alloy molten pool move.

Citation Information

Patent Citations

  • Low-cost and high-strength Ti-Zr-Al-F2 alloy

    CN104762526A

  • Titanium alloy plate, manufacturing method for titanium alloy plate, copper foil manufacturing drum, and manufacturing method for copper foil manufacturing drum

    CN113165032A

  • Method for preparing TA22 titanium alloy cast ingot

    CN113957278A

  • Titanium plate

    CN116635562A

  • Preparation method of large-size TC20 titanium alloy cast ingot

    CN118932204A

Cited By

  • A low-cost medium-strength high-plasticity titanium alloy and a preparation method of a titanium alloy plate

    CN122648778A